The Influence of Transformational Leadership and Supervisory Style on The Quality Of Primary School Teachers' Services - Mansyur, Mansyur; Akib, Akib (Shautut Tarbiyah-IAIN Kendari, 2024)
The purpose of this article is to show how transformational leadership and supervision influence the quality of teacher services. Data were analyzed using path analysis with ninety-five teachers as the units of analysis. The findings indicate both direct and indirect effects on each sub-construct. Substructure 1 includes: 1) the effect of transformational leadership on the quality of elementary school teacher services is 0.24 or 24%. 2) In substructure 2, the effect of transformational leadership on the quality of services achieved by supervisors is 0.32 or 32%. 3) the effect of transformational leadership on supervision is 0.48 or 48%. 4) the indirect effect of transformational leadership on the quality of teacher services through supervision is found to be significant at 4.978 with a P-Value = 0.000. Meanwhile, the indirect effect is 0.115 while the total effect is 0.355 or 35.5%. This study shows that the quality of services is influenced by changes in transformational leadership and supervision. Thus, these two factors can be considered in improving the quality of elementary school teacher services. Keywords: Transformational Leadership Style, Supervisor, Teacher Service Quality